Life cycle assessment of thermally treated and untreated maritime pine boards: a Portuguese case study - Ferreira, J. (2014)
The main aim of this Life Cycle Assessment (LCA) study was to assess and compare the environmental impacts of thermally treated and untreated maritime pine boards to be used as cladding. All processes were considered from forest management and resource extraction until cladding construction and its use during the next 15 years. At the end of the claddings life cycle it has been considered that the pine boards will be used as wood fuel to substitute firewood in the local heating system. The ReCiPe-V1.08 was the method selected for Life Cycle Impact Assessment of the products. The foreground data came from a Portuguese company that uses the ThermoWood method to thermally treat the pine boards and the background data came from the databases embedded in the SimaPro software. LCA results from the study have shown that the ´Ecosystems´ is the most important damage category mainly due to ´Agricultural land occupation´ by the wood in the forest. The cladding made by pine boards thermally treated can be considered more environmental friendly than the cladding made by untreated pine boards unless a very high weight (very close to 100 %) is given to impacts on ´Human health´ and ´Resources´ while a very low weight (very close to 0 %) is given to impacts on ´Ecosystems´. The study has also demonstrated an increase of potential environmental advantages of the thermally treated pine boards if wood energy is used in the heat treatment process instead Liquefied Petroleum Gas.